Gender in Japanese Popular Culture Rethinking Masculinities and Femininities - Salenius, Sirpa (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This open-access essay collection brings together a range of viewpoints on gender from a diverse group of international scholars, proposing different ways to think about gender, sexuality, and masculinities/femininities. By using case studies from Japanese popular culture, the authors contribute to the ongoing transnational discussion on gender performativity, examining ways in which gender may be constructed and contested. The multidisciplinary work will be of interest to scholars working in gender studies, Asian studies, and popular culture. It will also act as a source text for higher education courses in Asia, Europe, and the United States. Sirpa Salenius is Senior Lecturer at the University of Eastern Finland, Finland. Her research focuses on issues related to race, gender, and sexuality, from the nineteenth century to the present. Her other edited works include Race and Transatlantic Identities (2017), TransAtlantic Conversations (2017) and Neglected American Women Writers of the Long Nineteenth Century (2021).